2018
DOI: 10.1055/s-0037-1610199
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Rose Odorants: Serendipitous Discovery and Unique Olfactory Properties of 2,2-Bis(prenyl)-3-oxobutyronitrile and Its Derivatives

Abstract: 2,2-Bis(3-methylbut-2-enyl)-3-oxobutanenitrile [2,2-bis(prenyl)-3-oxobutyronitrile], an unusual bifunctional nitrile odorant with a fruity rosy, green odor was found to exhibit surprising differences in its detection thresholds (0.25 ng/L air for hyperosmics; 19 ng/L air for hyposmics) and perceived odor characters. To investigate this remarkable phenomenon, 13 derivatives of 2,2-bis(3-methylbut-2-enyl)-3-oxobutanenitrile were synthesized by either monoalkylation of 3-oxo-2-phenylbutanenitrile, or by dialkylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[4] Involved in an exciting total synthesis project, we realized that an early intermediate in the first-generation route exhibited a pleasant smell reminiscent of rose. [5] Closer investigation in collaboration with P. Kraft from Givaudan revealed that our synthetic intermediate 1 showed a rare feature in that both the quantity and the quality of the odor perception varied among two groups of panelists that were involved in its assessment (Fig. 1A).…”
Section: Introductionmentioning
confidence: 98%
“…[4] Involved in an exciting total synthesis project, we realized that an early intermediate in the first-generation route exhibited a pleasant smell reminiscent of rose. [5] Closer investigation in collaboration with P. Kraft from Givaudan revealed that our synthetic intermediate 1 showed a rare feature in that both the quantity and the quality of the odor perception varied among two groups of panelists that were involved in its assessment (Fig. 1A).…”
Section: Introductionmentioning
confidence: 98%